Effect of nozzle shape on fluid flow and heat transfer characteristics of an impinging jet system – a numerical study - Allauddin, Usman; Naeemullah; Verdin, Patrick G. (EDP Sciences, 2024)
Impinging jet is one of the most efficient techniques to achieve a high heat transfer coefficient and is used in many engineering applications. The present study focuses on the effect of nozzle shape on fluid behavior and heat transfer characteristics. For the current investigation, circular, square, rectangular, and elliptical nozzles with identical hydraulic diameters are used with Reynolds number Re ranging from 15,000–35,000. The circular nozzle results are validated with the published numerical and experimental data. In the current study, it is found that as the Reynolds number increases, the value of the averaged Nusselt number increases in all circumstances. When examining the different nozzle shapes, the value of the averaged Nusselt number is higher when an elliptical nozzle is used. The contours of the surface Nusselt number and velocity streamlines are also presented. The contour shows that the heat flux is highest in the stagnation zone and gradually decreases to the sides because they are outside the impingent coverage. Moreover, the area between the jets has a low heat flux. The heat transfer in the impinging zone is initially raised as the jet-induced crossflow increases and achieves a peak value, and then reduced stream-wise because of the crossflow effect.